Title: Ethical consequences in business decision process - Andreas, Karaoulanis (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
In this paper, the author tries to present the ethical dilemma in business decision process in Greeces frustrating economic environment. The author used the SSD decision approach in order to establish the theoretical background provided in terms of decision making and consequences.